2010
DOI: 10.1038/sj.bjc.6605997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of management of desmoid tumours associated with familial adenomatous polyposis in Dutch patients

Abstract: Background:The optimal treatment of desmoid tumours is controversial. We evaluated desmoid management in Dutch familial adenomatous polyposis (FAP) patients.Methods:Seventy-eight FAP patients with desmoids were identified from the Dutch Polyposis Registry. Data on desmoid morphology, management, and outcome were analysed retrospectively. Progression-free survival (PFS) rates and final outcome were compared for surgical vs non-surgical treatment, for intra-abdominal and extra-abdominal desmoids separately. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 28 publications
0
62
0
Order By: Relevance
“…However, the resection range should be properly enlarged to such tumors as desmoids, chondroma and osteoclastoma, or be resolved as in malignant tumors, though with benign pathological examinations (Errani et al, 2010;Nieuwenhuis et al, 2011). Chest wall resection can bring about different degrees of chest wall defects, which need to be repaired and reconstructed (Munhoz et al, 2011;Maeda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the resection range should be properly enlarged to such tumors as desmoids, chondroma and osteoclastoma, or be resolved as in malignant tumors, though with benign pathological examinations (Errani et al, 2010;Nieuwenhuis et al, 2011). Chest wall resection can bring about different degrees of chest wall defects, which need to be repaired and reconstructed (Munhoz et al, 2011;Maeda et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen articles that did not provide clear comparative data for each group were excluded from further analysis [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] .…”
Section: 22mentioning
confidence: 99%
“…Radical excision is often a therapeutic challenge or even impossible for intra-abdominal desmoids, confirmed by previous and recent studies which reported a rather low success rate of radical removal of intra-abdominal or retroperitoneal desmoids (8,32,91,107,(113)(114)(115)(116).…”
Section: Special Surgical Considerations By Intra-abdominal Desmoid Tmentioning
confidence: 73%
“…The optimal therapy for desmoids is difficult to be established due to the heterogeneous clinical behavior and anatomical presentation associated to the variable etiology, the high local recurrence rate, the infilltrative growth and the rarity of the tumor (8,15,91). There is limited or no evidence based medicine supporting treatment choice (5,7,8,15,85 …”
Section: Treatment Of Desmoid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation